2022
DOI: 10.1038/s41380-022-01452-7
|View full text |Cite
|
Sign up to set email alerts
|

Subtly altered topological asymmetry of brain structural covariance networks in autism spectrum disorder across 43 datasets from the ENIGMA consortium

Abstract: Small average differences in the left-right asymmetry of cerebral cortical thickness have been reported in individuals with autism spectrum disorder (ASD) compared to typically developing controls, affecting widespread cortical regions. The possible impacts of these regional alterations in terms of structural network effects have not previously been characterized. Inter-regional morphological covariance analysis can capture network connectivity between different cortical areas at the macroscale level. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 93 publications
0
26
0
Order By: Relevance
“…Last, we aimed to understand the degree to which cortical alterations observed in individual disorders are reflected in described transdiagnostic features. To this end, we first examined cross-cortical similarities of illness effects within disorders 101 , 102 , via absolute differences in Cohen’s d values between regions. We then correlated each parcel’s disorder-specific whole-brain covariance profile with the previously described transdiagnostic covariance profile of the same parcel.…”
Section: Methodsmentioning
confidence: 99%
“…Last, we aimed to understand the degree to which cortical alterations observed in individual disorders are reflected in described transdiagnostic features. To this end, we first examined cross-cortical similarities of illness effects within disorders 101 , 102 , via absolute differences in Cohen’s d values between regions. We then correlated each parcel’s disorder-specific whole-brain covariance profile with the previously described transdiagnostic covariance profile of the same parcel.…”
Section: Methodsmentioning
confidence: 99%
“…We found that cord blood treatment was associated with changes in connectivity among a number of networks connected to the dlPFC. The dlPFC is a critical hub for supporting attention, memory, and other aspects of cognition in the brain and has been implicated as a critical region in the neurobiology of autism ( 62 , 63 ). Studies employing resting state MRI have demonstrated that differential connectivity in networks involving the dlPFC correlate with social and communication abilities in autistic children ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of ASD remain unknown, and studies have focused on genomics, metabolomics [ 4 ], and imaging investigations [ 5 ]. Abnormalities in lipid metabolism contribute to the pathogenesis of ASD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%